You "Cantu": Multidisciplinary Collaboration Resulting in Successful Orthognathic Surgery. (February 2020) - Kurian, Christopher; Pinamonti, Gina; Starling Hughes, Susan; Martin, Julie; Lypka, Michael
Cantú syndrome (CS) is a rare autosomal dominant disorder caused by a heterozygous pathogenic variant in the ABCC9 or KCNJ8 gene. The disorder is characterized by congenital generalized hypertrichosis, coarse acromegaloid facial features (broad nasal bridge, epicanthal folds, wide mouth, macroglossia), skeletal abnormalities (calvarial thickening, metaphyseal flares, coxa valga, scoliosis), tortuous vasculature (meningeal arteriovenous malformations), and cardiac abnormalities (patent ductus arteriosus, pericardial effusion). Despite the constellation of craniofacial features, there are currently no documented cases of a patient with CS having orthognathic surgery. The purpose of this report is to highlight the multidisciplinary collaboration, including establishment of a genetic diagnosis, cardiac management, and orthodontic therapy, in performing successful orthognathic surgery in a patient with CS.